Visual-motoric Integration in Different Forms of Infantile Cerebral Palsy (ICP) - Mihilewicz, Stanisława (INSTED: Interdisciplinary Studies in Education & Society, 1998)
The article reports the results of examinations of 40 children with infantile cerebral palsy (ICP) with normal mental development and 40 children fully psychically able with the same intellectual development. The examinations concerned the visual-motoric integration for different forms of infantile cerebral palsy. The characteristics of infantile cerebral palsy determines the kind of neurological disorders, their location and symptoms. The method and technique of the examinations were presented along with the mechanics of visual-motoric integration. Also the term of ?integration? was presented in different contexts. Based on the structure of the Scheme of body and face in the ?en face? test an analysis of the results was made and an interpretation of conclusions was made, which show what form of ICP favourably influences the process of visual-motoric integration.